Building a business with a beat leadership lessons from Jazzercise : an empire built on passion, purpose, and heart - Missett, Judi Sheppard 1944-; McCarthy, Susan Carol (McGraw-Hill Education, 2019)
"Proven methods for turning any passion into major profits - from the legendary entrepreneur who turned her idea into a USD100 million global powerhouse. For the first time ever, the founder and CEO of Jazzercise, Inc., reveals the secrets to her staggering success. In Building a Business with a Beat, Judi Sheppard Missett describes the principles that made, and continue to make, Jazzercise the worldwide women-owned enterprise it is today. You'll learn how to build a business devoted to excellence and communal satisfaction, while being inspired by the author's story of turning a class of 15 people in a Chicago dance studio into the world's leading dance fitness program. Sheppard Missett shows how you can build your own successful business by: daring to dream big, pairing your passion with a greater purpose, paying attention to cues, signs and signals, embracing changing technologies, hiring for attitude, empathy, and creativity, setting standards, establishing "firsts", cultivating your customer community, reaching out, stepping forward, and giving back"--
Description based on print version record
Keywords: Jazzercise, Inc; Small business -- Growth; Success in business; New business enterprises; Petites et moyennes entreprises; Croissance; Succès dans les affaires; Nouvelles entreprises; BUSINESS & ECONOMICS / Entrepreneurship; Small business; Growth